Analisis Implikatur Dalam Tuturan Slang Remaja di Media Sosial - Muchibbatul Uchriyah; Mimas Ardhianti (sarasvati, 2026)
The development of social media has created various forms of slang language widely used by teenagers to express identity, emotions, and social attitudes. In its use, slang often contains implied meanings in the form of implicatures, making it interesting to study from a pragmatic perspective. This study aims to describe conventional implicatures and conversational implicatures in teenagers’ slang utterances on social media. The research uses a descriptive qualitative approach with slang utterances on social media platforms as the object of study. The data consist of slang expressions containing implicatures found in comments, captions, statuses, and digital conversations on TikTok, Instagram, WhatsApp, and Twitter (X) during 2025. Data were collected through documentation and note-taking techniques and analyzed through identification, classification, and interpretation based on Grice’s implicature theory. The results show that conventional implicatures appear through commonly understood slang vocabulary, while conversational implicatures depend on context and often function as satire, criticism, or evaluation.